Energy storage systems in the context of Nepal - Dhakal, Prabin; Bhatta, Geeta; Karki, Rashmi; Khatiwada, Dilip; Lohani, Sunil Prasad (Journal of Innovations in Engineering Education, 2024)
Energy storage is essential for managing the reliability of renewable energy by responding to fluctuations of energy systems. With the dominance of hydropower, constituting 95% of Nepal's generation capacity, mostly by run-of-river, energy storage systems (ESS) are vital not only during dry seasons but also to address vulnerabilities of hydropower stations during the rainy season. Moreover, Nepal’s inadequate commitment to diversifying the energy mix, particularly with a focus on modern renewables along with effective energy storage solutions pose a severe threat to energy security of the country. This paper aims to analyze the distinctive characteristics of numerous ESS and their applicability in Nepal in terms of size, operation, cost and lifetime. Based on a comprehensive literature review, it's evident that Pumped Hydro Energy Storage (PHES), would be promising ESS for large-scale (MWh to GWh) and diurnal to seasonal use. This is due to higher round-trip efficiency (above 80%), lower capital cost per unit energy storage, and matured technology having strong competence in Nepal. Nepal’s long experience in hydropower and having several on-river and over 2800 potential off-river PHES sites make PHES promising technology for energy independence and reliable energy system in Nepal.